Puszcza Pilicka jako teren polowań reprezentacyjnych Prezydenta RP - Zwoliński, Piotr (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2009)
The area of Pilica Forest covers the terrains where forest inspectorates of Opoczno, Smardzewice and Spała are situated. The forests made up a compact complex of varied stand divided with the Pilica river. After achieving independence during the First World War a Representative Residence of the Polish President was created in Spała. The village was the place of work and rest of the President. It was also the place of state ceremonies and the neighbouring forests were the place of representative huntings for guests from the country and abroad.